Tetramethylpyrazine enhances neuroprotection and plasticity in cerebral ischemia-reperfusion injury via RhoA/ROCK2 pathway inhibition - Zhang, Yixin; Zhang, Xin; Shi, Xiaocheng; Liao, Weijing; Lin, Junbin (Frontiers in Pharmacology, 2025)
Tetramethylpyrazine (TMP) is an active component of the Chuanxiong, effectively crosses blood-brain barrier (BBB). It exhibits neuroprotective potential in cerebral ischemia-reperfusion injury (CIRI). This study performed middle cerebral artery occlusion/reperfusion (MCAO/R) surgery in rats to evaluate TMP’s efficacy and mechanisms in mitigating CIRI. Rats received intraperitoneal TMP (40 mg/kg) for 3 days prior to MCAO/R and continued for 14 days post-surgery. Behavioral tests were conducted using mNSS and Morris water maze tests. Histopathological analyses, including HE, Nissl, and TUNEL staining. mRNA sequencing revealed that RhoA and ROCK2 were upregulated in the CIRI model and downregulated by TMP treatment. GO enrichment and KEGG enrichment showed RhoA and ROCK were related to neuroplasticity. Western blot and immunofluorescence staining confirmed that TMP inhibited RhoA, ROCK2, phosphorylated LIMK, and phosphorylated cofilin expression. Additionally, TMP increased the levels of neuroplasticity-related proteins PSD95 and MAP2, promoting synaptic and dendritic regeneration. Administration of lysophosphatidic acid (LPA), a RhoA/ROCK pathway agonist, attenuated TMP’s neuroprotective effects, validating the pathway’s role in TMP-mediated protection. These findings indicate that TMP confers neuroprotection in CIRI by inhibiting the RhoA/ROCK pathway and enhancing neuroplasticity, underscoring its therapeutic potential in CIRI.